FLUKTUASI EKSPOR KARET ALAM INDONESIA KE TIONGKOK TAHUN 2012-2016 - Hajrah "; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to explain factors influence the fluctuation of Indonesian natural rubber export to China in 2012-2016 Rubber is one of the crops that has an important role in the economic activities in Indonesia. Rubber is one of the prominent export commodities in the country, besides oil and gas. This research uses a export theory, liberalism perspective, which is then supported by nation-state analysis level. The methodology using a qualitatve method and collecting the data using a library research literature.The results of this study are the occurrence of fluctuations in Indonesian rubber exports to Tiongkok which are influenced by internal and external factors. Internal factors are domestic rubber prices and the level of domestic rubber production. Meanwhile, the internal factor are the international price of rubber, the exchange rate of the rupiah against the Chinese yuan, the gross domestic product of Tiongkok, the International Tripartite Rubber Council (ITRC) policy and the level of rubber consumption in Tiongkok.  Keywords: Exports, Liberalism Perspective, Fluctuations, Natural Rubber